Altered intrinsic brain activity in patients with hepatic encephalopathy. Issue 5 (13th February 2021) - Cao, Yuan; Wu, Baolin; Chen, Taolin; Diao, Wei; Jia, Zhiyun
Abstract: Neuropsychiatric deficits are common in patients with liver cirrhosis (LC), especially in those with hepatic encephalopathy (HE). Previous studies reveal abnormalities in brain activity underlying the neuropsychiatric deficits in LC patients; however, the results are inconsistent. We conducted a meta‐analysis of resting‐state functional magnetic resonance imaging studies using anisotropic effect‐size signed differential mapping software on LC patients to characterize the most consistent regional activity alterations, and to evaluate the potential effect of liver transplantation (LT) on brain function. Meta‐regression analyses were performed to explore the relationship between brain alterations and clinical variables. Compared with healthy controls, the typical patterns of increased regional activity in the fronto‐striato‐cerebellar network and decreased activity in the visuo‐sensorimotor network and cingulate gyrus were identified in LC patients, which remained significant in the subgroup meta‐analyses of minimal HE (MHE) and overt HE (OHE) patients. Functional deficits in the default mode network (DMN) were found in OHE patients compared with MHE patients. Ammonia level positively correlated with brain activity in the right middle temporal gyrus, and the completion time of number connection test A negatively correlated with brain activity in the left anterior cingulate gyrus. In addition, patients showed increased activity in the visuo‐sensorimotor network and precuneus after LT. Our study suggests that alterations in the fronto‐striato‐cerebellar and visuo‐sensorimotor networks may be the potential pathophysiological mechanisms underlying HE, and deficits in the DMN may indicate the progression of HE. LT may improve brain function in the visuo‐sensorimotor network. This study has registered in the PROSPERO (CRD42020212758). Abstract : Hepatic encephalopathy (HE) is a severe neuropsychiatric complication of live cirrhosis. We identified the typical patterns of increased regional activity in the fronto‐striato‐cerebellar network and decreased activity in the visuo‐sensorimotor network and cingulate gyrus in HE patient.